2004
DOI: 10.1111/j.0269-283x.2004.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and economic importance of infestations with Sarcoptes scabiei and Haematopinus suis in sows of pig breeding farms in Hesse, Germany

Abstract: A cross-sectional survey was performed in 110 randomly selected pig-breeding farms of southern Hesse, Germany to estimate the prevalence of ectoparasite infestations and to find possible risk factors. Ear scrapings of, if available, 10 sows per farm were examined for Sarcoptes scabiei var. suis (De Geer) (Acaridida: Sarcoptidae) by the potassium hydroxide digestion method, and a total of 2754 sows was inspected for skin lesions and infestations with Haematopinus suis (L.) (Anoplurida: Haematopinidae). Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 14 publications
1
32
2
4
Order By: Relevance
“…From Ghana 38.2 % pigs have been reported as infested with Saroptes suis (Permin et al 1999). The prevalence of the infestation from Germany has been recorded as 45.4 % (Damriyasa et al 2004). Alonso de Vega et al (1998) reported 37 % of the 1,318 slaughtered pigs of southeastern Spain examined were found positive for S. scabiei var.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…From Ghana 38.2 % pigs have been reported as infested with Saroptes suis (Permin et al 1999). The prevalence of the infestation from Germany has been recorded as 45.4 % (Damriyasa et al 2004). Alonso de Vega et al (1998) reported 37 % of the 1,318 slaughtered pigs of southeastern Spain examined were found positive for S. scabiei var.…”
Section: Prevalencementioning
confidence: 99%
“…For this, pig owners are generally concerned about the internal parasitic infections and ignored the external parasitic infestations. But external parasitic infestations particularly mange mite infestation in pigs are very much important because of its economic significance (Damriyasa et al 2004). Sarcoptic mange infestation in pigs are caused by the mite Sarcoptes scabies var.…”
Section: Introductionmentioning
confidence: 99%
“…A maior parte dos dados de prevalência para S. scabiei observados em outros países e em outras regiões no Brasil foram muito superiores aos encontrados nas Granjas de Reprodutores de Suídeos Certificadas (GRSC) deste estudo, provavelmente por terem sido realizados em granjas comerciais e criações caseiras e não em granjas de reprodutores certificadas que, obrigatoriamente, devem ser livres do ácaro (SABIITI et al, 1979;GUTIERREZ et al, 1996;VEGA et al 1998;SILVA, 2002;HOLMGREN e WALLGREN, 2003;DAMRIYASA et al, 2004 ).…”
Section: Discussão E Conclusãounclassified
“…Nos Estados Unidos, 25,30% na região central e 22,50% no noroeste do país foram positivos (SABIITI et al, 1979), e em granjas comerciais de suínos na Suécia a prevalência foi de 22% (HOLMGREN, 2003). As propriedades comerciais do sul da Alemanha apresentaram a menor prevalência, com 19,1% de animais positivos (DAMRIYASA et al, 2004).…”
Section: Introductionunclassified
See 1 more Smart Citation